Development of Colon Targeted Extended Drug Delivery System for Mebendazole Using Grafted Natural Polymers - Chandakavathe, Baburao Nanasaheb; Kulkarni, Ravindra; Rajmane, Akash Dadanna; Mane, Snehal Limbraj; Waykule, Nishigandha Jayant (Indian Journal of Pharmaceutical Education and Research, 2024)
Background Even though the natural polymers are biodegradable, non-toxic and cost effective, but these suffer with some of drawbacks like uncontrolled drug release, enzymatic degradation, reduction in viscosity on long term storage, thermal instability etc. The aforesaid limitations can be overcome by grafting of natural polymers to obtain high performance biomaterials for drug delivery system. Materials and Methods Purified fenugreek and mesquite gums were grafted with acrylamide using Ceric Ammonium Nitrate (CAN) as free radical initiator. Confirmation of grafting was done by elemental analysis and FT-IR spectroscopy. Grafted copolymers were tested for its biodegradability in microorganisms and toxicity in Drosophila melanogaster. Nine batches of mebendazole tablets (F1 to F9) were prepared using mixture of acrylamide grafted fenugreek and mesquite gum polymer by 32 factorial designs. Compressed tablets were tested for post-compression compendia parameters. Results FT-IR confirmed the grafting and compatibility between drug and synthesized copolymers. Synthesised graft copolymers showed significant swelling index, water retention capacity, viscosity, hydration capacity than the pure gum polymers. Compressed tablets showed hardness (5.5 to 6.6 kg/cm2), friability (less than 1%). thickness (3 mm) and complied weight variation test as per compendial standards. Further tablets were coated with Eudragit RS 100 demonstrated small amount of drug release in 5 hr and maximum amount of drug released in colonic region. Hence, after reaching colonic region drug release extended upto 12 hr due to satisfactory drug release by copolymers. Conclusion Grafted copolymers were biodegradable, non-toxic and showed higher swelling index then pure polymers. These copolymers can be used as drug release retardant in the tablet formulation.
Keywords: Grafting; Fenugreek gum polymer; Mesquite gum polymer; Helminthiasis; Drosophila melanogaster; Elemental analysis